(untitled) - Oda, Shigeru (Leyden, 1969)
Contents: Coastal fishery jurisdiction; control of the high-seas fishery resources; special treatment of sendentary fisheries;...
Keywords: Bảo tồn tài nguyên biển,Marine resources conservation